Combined operando X-ray diffraction–electrochemical impedance spectroscopy detecting solid solution reactions of LiFePO(4) in batteries - Hess, Michael (Nat Commun, 2015)
Lithium-ion batteries are widely used for portable applications today; however, often suffer from limited recharge rates. One reason for such limitation can be a reduced active surface area during phase separation. Here we report a technique combining high-resolution operando synchrotron X-ray diffraction coupled with electrochemical impedance spectroscopy to directly track non-equilibrium intermediate phases in lithium-ion battery materials. LiFePO(4), for example, is known to undergo phase separation when cycled under low-current-density conditions. However, operando X-ray diffraction under ultra-high-rate alternating current and direct current excitation reveal a continuous but current-dependent, solid solution reaction between LiFePO(4) and FePO(4) which is consistent with previous experiments and calculations. In addition, the formation of a preferred phase with a composition similar to the eutectoid composition, Li(0.625)FePO(4), is evident. Even at a low rate of 0.1C, ∼20% of the X-ray diffractogram can be attributed to non-equilibrium phases, which changes our understanding of the intercalation dynamics in LiFePO(4).